Lead, Cadmium, Zinc, and Copper Bioavailability in the Soil-Plant-Animal System in a Polluted Area - Violina R. Angelova; Radka V. Ivanova; Jivko M. Todorov; Krasimir I. Ivanov (The Scientific World Journal)
A comparative research study on the bioavailability of Pb, Cd, Zn, and Cu in the soil-plant-animal-system was carried out. The connection between the total quantity and the mobile forms of Pb, Cd, Zn, and Cu in soils with different levels of contamination; the transition of these metals into rapeseed; and their assimilation by rabbits fed with a food that consisted mainly of rapeseed was studied. It was established that the absorption of heavy metals by the rapeseed definitely has a selective character, as the affinity towards Zn is most strongly expressed. The accumulation of Pb, Cd, Zn, and Cu in the organs of the rapeseed occurs in the following order: inflorescences > leaves > stems. A direct connection between the quantity of the mobile forms and their accumulation in the plants was not found. The environmental contamination has a significant effect on heavy metal levels and distribution, as the largest quantity of all four elements is accumulated in the kidneys and liver. A well-expressed impact of the level of Cd contamination on the absorption of essential trace metals (Zn and Cu) and their accumulation into some of the organs of the animals was found.